APPLICATION OF MICROTREMOR ARRAY METHODS TO DETERMINE THE STRUCTURE IN THE BELOW THE SURFACE SOIL LAYER BASED ON SWAVE VELOCITY (VS) - CHRISTOPHER SIMANJUNTAK (NIM : 10212015), FREDERICK
Earth physics is the study of earth things in accordance with the principles of physics. Earth Physics be initial guidance to determine the subsurface structure and physical properties which is contained in the layers. Estimation of the surface layer of the earth as well as its physical properties can be determined by utilizing the seismic wavemethod. Utilization of thismethod is divided into two, active seismic method and passive seismic method. One part of passive seismic wave method is to utilize microtremor wave. This research will used microtremor with microtreomor array method using SPAC theory (Spatial Auto Correlation Method). This research will be Measures in the field with a particular array shape then the data obtained will be processed to obtain dispersion curveswave velocity and frequency to be processed by inverse modeling in order to determine the underground layers tructure of the measuring area. The results obtained by the measurement data processing in the area. Negeri Lima, Ambon, Maluku Utara, At a depth of 0 - 6.64 m have the S wave velocity (Vs) 216-298 m/s, At a depth of 6.64 - 35.5 m has the S wave velocity Vs)325-470 m/s, At a depth of 35.5 - 169.2 m have the s wave velocity (Vs) 841-1022 m/s, At a depth of 169.2 - 217.3 m have the s wave velocity (Vs)1563 m/s, At a depth of 217.3 - 469.9 m speed s wave propagation (Vs) 1992 m /s